SIMRS Analysis In The Patient Registration Section Using The PIECES Method At Panti Waluyo Hospital - Hasna Khoirunnisa Putri; Wahyu Wijaya Widiyanto; Ahmad Sunandar (Journal Health Information Management Indonesian (JHIMI), 2024)
The rapid development of today's technology has a big influence on people's lives and in the health sector. The application of this technology plays an important role in today's health sector. Almost all health institutions utilize information systems in their services. A hospital is a health service that requires fast, accurate and reliable service when serving patients. SIMRS is an information system that is applied digitally in the process of providing health services to patients, to obtain accurate data. To make the analysis easier, one of the methods used for analysis is the PIECES framework, where this framework outlines 6 analysis factors consisting of performance, information, economy, control, efficiency and service. Based on the results of SIMRS analysis research in the Outpatient Registration section using the PIECES Method at Panti Waluyo Hospital, it can be concluded that: 1. SIMRS in terms of Information, Economy, Control (Security), Efficiency, The service supports the service and is in accordance with the patient's needs. 2. In terms of performance, it is very supportive of service, but obstacles are still found when SIMRS experiences a server down error, service takes 20 minutes when it should only take less than 5 minutes.